Can EPS Development be Avoided with Early Interventions? The Potential Role of Tamoxifen—A Single-Center Study. Issue 6 (September 2014) - De Sousa–Amorim, Erika; Del Peso, Gloria; Bajo, M. Auxiliadora; Alvarez, Laura; Ossorio, Marta; Gil, Fernando; Bellon, Teresa; Selgas, Rafael
Background: Encapsulating peritoneal sclerosis (EPS) is a severe complication of peritoneal dialysis (PD). Identification of patients at high risk for EPS ("EPS-prone") and delivery of appropriate interventions might prevent its development. Our aim was to evaluate the clinical characteristics and outcomes of all EPS and EPS-prone patients diagnosed at our PD unit. Methods: For a 30-year period representing our entire PD experience, we retrospectively identified all patients with EPS (diagnosed according to International Society for Peritoneal Dialysis criteria) and all patients defined as EPS-prone because they met at least 2 established criteria (severe peritonitis, PD vintage greater than 3 years, severe hemoperitoneum, overexposure to glucose, and acquired ultrafiltration failure). Results: Of 679 PD patients, we identified 20 with EPS, for an overall prevalence of 2.9%. Mean age at diagnosis was 50.2 ± 16.4 years, with a median PD time of 77.96 months (range: 44.36 – 102.7 months) and a median follow-up of 30.91 months (range: 4.6 – 68.75 months). Of patients with EPS, 10 (50%) received tamoxifen, 10 (50%) received parenteral nutrition, and 2 (10%) underwent adhesiolysis, with 25% mortality related to EPS. Another 14 patients were identified as EPS-prone. Median follow-up was 54.05 months (range: 11.9 – 87.04 months). All received tamoxifen, and 5 (36%) received corticosteroids; none progressed to full EPS. We observed no differences in baseline data between the groups, but the group with EPS had been on PD longer (84 ± 53 months vs 39 ± 20 months, p = 0.002) and had a higher cumulative number of days of peritoneal inflammation from peritonitis (17.2 ± 11.1 days vs 9.8 ± 7.9 days, p = 0.015). Overall mortality was similar in the groups. The incidence of EPS declined during our three decades of experience (5.6%, 3.9%, and 0.3%). Conclusions: Being a serious, life-threatening complication of PD, EPS requires high suspicion to allow for prompt diagnosis and treatment. Early detection of EPS-prone states and delivery of appropriate intervention might prevent EPS development. Tamoxifen seems to be a key strategy in prevention, but caution should be used in interpreting our results. Additional randomized controlled studies are needed.